Transition metal deposition on graphene and carbon nanotubes - Suarez-Martinez, Irene; Felten, A.; Pireaux, J.; Bittencourt, C.; Ewels, C. (American Scientific Publishers, 2009)
We present a combined theoretical and experimental comparative study of the deposition of five different metals on perfect and defective graphene and multi-walled carbon nanotubes (MWNTs): Ti, Ni, Pd, Pt and Au. Atomistic modelling successfully provides a comprehensive picture of surface binding, diffusion and aggregation properties for these metals, highlighting some fundamental differences in their surface chemical and electronic behaviour. We correlate these theoretical results with experimental TEM images of metal deposited MWCNTs. Copyright © 2009 American Scientific Publishers.